Tüketici davranışlarında durumsal faktörlerin satın alma niyeti ve memnuniyet üzerindeki etkisi ve bir araştırma - Bilgen, İlknur (My University, 2011)
ketici Davranışları, Durumsal Faktörler, Satın Alma Niyeti, Memnuniyet ÖZET TÜKETİCİ DAVRANIŞLARINDA DURUMSAL FAKTÖRLERİN SATIN ALMA NİYETİ VE MEMNUNİYET ÜZERİNDEKİ ETKİSİ VE BİR ARAŞTIRMA Bugün pazarda hakim gücün tüketicilerin elinde olduğu yadsınamaz durumdadır. Hatta, içinde bulunduğumuz yüzyıl, “Tüketici Yüzyılı” olarak tanımlanmaktadır. Firmalar için, böylesine önemli bir güce sahip olan tüketicilerin nasıl davranacaklarını belirlemek, son derece önemlidir. Bugün firmalar, tüketicilerin kara kutularını çözmeye çalışarak, ürün ve hizmetlerini bu yönde üretmektedirler. Tüketici davranışlarını etkileyen birçok farklı faktör bulunmaktadır. Bunlar; kültür ve alt kültür, sosyal sınıflar, referans grupları, roller ve aile gibi sosyal faktörler, motivasyon, algılama, öğrenme, tutumlar ve kişilik gibi psikolojik faktörler ve demografik faktörler ve durumsal faktörler gibi kişisel faktörlerdir. Bu çalışmada ele alınan durumsal faktörler, tüketici davranışları üzerinde önemli bir etkiye sahiptir. Durumsal faktörler, fiziksel etkiler, sosyal etkiler, zaman boyutu, amaç boyutu ve anlık etkilerden oluşmaktadır. Key Words:Consumer Behavior, Situational Factors, Purchase Intention, Satisfaction

THE EFFECT OF SITUATIONAL FACTORS ON PURCHASE INTENTION AND SATISFACTION IN CONSUMER BEHVIOR AND A RESEARCH It is an undeniable fact that today the dominant power in the market is with the consumers. Furthermore this century is called as the “Century of Consumers”. For the companies it is very vital to determine how the consumers behave having so much power at hand. Today the companies try to decipher the codes of the consumers and thus produce their products and services. There are many factors having impacts on consumer behaviors. These factors are; social factors such as culture and sub-culture, social classes, reference groups, roles and family; psychological factors such as motivation, perception, learning, attitudes and personality and personal factors such as demographical factors and situational factors. The situational factors analyzed within this study have essential impacts on the consumer behaviors. The situational factors are comprised of physical factors, social factors, time dimension, task definition and antecedent states. In this study the determination of the most effective situational factors on purchase intention and satisfaction is aimed. In the present study performed with this objective, the most effective factor on purchase intention and satisfaction is determined as physical factors however in product groups different factors have also been revealed. The most effective situational factors on the purchase intention for the bread among the product groups are observed as antecedent states, whereas for the meat and meat products that is task definition, for fresh fruits and vegetables that is task definition, for the frozen foods they are physical factors, for the snack food they are antecedent states for the milk and milk products they are physical factors have been observed. When purchase intention is considered along with the conditional factors the most effective factors on satisfaction have been observed are time for bread, task definition for meat and meat products, purchase intention of fresh fruit and vegetables, task definition for frozen goods, task definition for snack and physical factors for milk and milk products.
Keywords: Müşteri Memnuniyeti; Satın Alma Davranışı; Tüketici Davranışları